HIDDEN GUARANTEE (GIRO) - Radić, Irena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Bearing in mind the great legal significance of the bill of exchange and its widespread use in domestic and international finance, the author determined to analyze the issue that has proven to be very controversial in practice. That is a so called hidden guarantee, when a person, factually a guarantor of a bill, doesn't place its signature on the bill as a guarantor, but formally takes the role of the drawer, the drawee/acceptor or the endorser. It seems that the last case of a hidden guarantee (a hidden guarantor as an endorser) is causing most of the issues for the banks, which requires girieren bills when granting loans, as well for the courts when deciding on this matter.Namely, it is disputable how to judge a situation when the first signature on the back of the bill is not a signature of a payee, but of a drawer or a person not otherwise a party to a bill. The courts attributed different meanings to this signature. On the one hand, there were courts that found this to be a guarantee, an endorsement or a so called hidden guarantee. On the other hand, there were courts that considered that the series of endorsements were interrupted by this signature and consequently that all of the subsequent endorsements were invalid. Therefore, in this paper the author will analyze provisions regarding a so called hidden guarantee in domestic law and the position of a hidden guarantor in each of the three cases of a hidden guarantee. Further, the author will present court’s jurisprudence in countries of the region and shed a light on contradictory judgments in regard to this matter.